2020
DOI: 10.1007/jhep01(2020)090
|View full text |Cite
|
Sign up to set email alerts
|

A Mellin space approach to cosmological correlators

Abstract: We propose a Mellin space approach to the evaluation of late-time momentumspace correlation functions of quantum fields in (d + 1)-dimensional de Sitter space. The Mellin-Barnes representation makes manifest the analytic structure of late-time correlators and, more generally, provides a convenient general d framework for the study of conformal correlators in momentum space. In this work we focus on tree-level correlation functions of general scalars as a prototype, including n-point contact diagrams and 4-poin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
204
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(215 citation statements)
references
References 100 publications
11
204
0
Order By: Relevance
“…Lastly, we hope our investigation can connect with cosmological bootstrap program as AdS and dS correlators are closely related. For instance, in [76,77] authors propose a framework for the computation of late-time correlators in de Sitter space and bridge the gap with the boundary correlators in anti-de Sitter space. Moreover, it has been shown that the wave function of the universe for conformally coupled scalar theories in dS 4 can be expressed as volumes of polytopes in the same spirit as the amplituhedron [78][79][80].…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, we hope our investigation can connect with cosmological bootstrap program as AdS and dS correlators are closely related. For instance, in [76,77] authors propose a framework for the computation of late-time correlators in de Sitter space and bridge the gap with the boundary correlators in anti-de Sitter space. Moreover, it has been shown that the wave function of the universe for conformally coupled scalar theories in dS 4 can be expressed as volumes of polytopes in the same spirit as the amplituhedron [78][79][80].…”
Section: Resultsmentioning
confidence: 99%
“…We note that, while conformal symmetry fixes the location of the poles in the Mellin integrand, the zeros, encoded in the sine function in (3.12), are fixed by the early time boundary conditions (Bunch-Davis in our case). The expression (3.12) is also obtained by simply evaluating the late-time correlator directly in de Sitter space using the Mellin-Barnes representation for the propagators [44]. Here, we directly evaluated the Fourier transform of the known result [99,100] for tree-level three-point Witten diagrams of scalar fields in Euclidean anti-de Sitter space (which is most naturally given by a Mellin-Barnes integral) and applying the dictionary spelled out in §2.5 to each propagator at the level of the Mellin integrand to obtain the corresponding late-time correlator in de Sitter space.…”
Section: General External Scalarsmentioning
confidence: 99%
“…More recently, Refs. [42,43] developed a Mellin representation of exchange diagrams on (anti-)de Sitter space in momentum space for external scalars with arbitrary mass. It would be interesting to explore the relation of these works with ours.…”
Section: Resultsmentioning
confidence: 99%